Does Religion Buffer the Negative Effects of Economic and Subjective Poverty on Life Satisfaction? Longitudinal Evidence from Hong Kong - Shi, Songyun; Peng, Chenhong; Zhang, Qian; Wen, Ming; Chen, Yu-Chih; Yip, Paul S. F. (Applied Research in Quality of Life, 2025)
Researchers have long been interested in the impact of poverty on life satisfaction, as well as in the buffering role of religion within this association. However, longitudinal evidence is limited, leaving uncertainties about how religion buffers this association, especially concerning the subjective aspect of poverty and in non-Christian-dominant societies. This study used two-wave panel data from Hong Kong ( N = 1,006), where more than half of the population identifies as having no religion and all major world faiths coexist peacefully. We employed the cross-lagged panel model (CLPM) to examine the longitudinal associations between economic poverty, subjective poverty, and life satisfaction while exploring the buffering effect of religion. The results of CLPM showed that subjective poverty had a long-term negative impact on life satisfaction, highlighting the pivotal role of social comparison in influencing individuals’ life satisfaction. Furthermore, religion was found to buffer the temporal association between subjective poverty and life satisfaction; this buffering effect persists within religious groups, regardless of religious attendance. This paper highlights the significance of subjective poverty in influencing life satisfaction and contributes to our understanding of whether and how religion matters to people’s life satisfaction among those experiencing poverty.